Epidemiology of Weaning From Invasive Mechanical Ventilation in Subjects With COVID-19. - Dorado, Javier H.; Navarro, Emiliano; Plotnikow, Gustavo A.; Gogniat, Emiliano; Accoce, Matías (Respiratory Care, 2023)
BACKGROUND: Patients requiring mechanical ventilation due to COVID-19 have different characteristics of evolution and outcome compared to the general ICU population. Although early weaning from mechanical ventilation is associated with improved outcomes, inadequate identification of patients unable to be weaned may lead to extubation failure and increased days on mechanical ventilation. Outcomes related to mechanical ventilation weaning in this population are scare and inconclusive. Therefore, the objective of this study was to describe the characteristics of mechanical ventilation weaning in subjects with acute respiratory failure induced by COVID-19. METHODS: This was a multi-center, prospective cohort study. We included adult subjects requiring at least 12 h of mechanical ventilation due to COVID-19 infection admitted to any participating ICUs. Characteristics of the mechanical ventilation weaning and extubation process, as well as clinical results, were the primary outcome variables. Weaning types were defined according to previously described and internationally recognized categories. RESULTS: Three hundred twenty-six subjects from 8 ICUs were included. A spontaneous breathing trial (SBT) was not performed in 52.1% of subjects. One hundred twenty-eight subjects were extubated, and 29.7% required re-intubation. All the subjects included could be classified by Weaning according to a New Definition (WIND) classification (group 0 = 52.1%, group 1 = 28.5%, group 2 = 8.0%, and group 3 = 11.3%) with statistically significant differences in duration of mechanical ventilation (P < .001) and ICU length of stay (P < .001) between groups. CONCLUSIONS: The mechanical ventilation weaning process in subjects with COVID-19 was negatively affected by the disease, with many subjects never completing an SBT. Even though temporal variables were modified, the clinical outcomes in each weaning group were similar to those previously reported.